1,6-carbene transfer: gold-catalyzed oxidative diyne cyclizations - Nösel, Pascal; Nunes dos Santos Comprido, Laura; Lauterbach, Tobias; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Journal of the American Chemical Society, 2013)
In the presence of a gold catalyst an unprecedented oxidative cyclization of diynes takes place. The reaction cascade is initiated by an oxygen transfer from a N-oxide onto a gold-activated alkyne. The formed α-oxo carbene is transferred across the second alkyne yielding a stabilized vinyl carbene/cation. Alkyl migration or sp3-CH insertion then terminates the catalytic cycle by formation of highly substituted functionalized indenones. A 1,6-carbene shift could be supported by the oxidation of the vinyl carbene. This protocol represents an attractive alternative to procedures which are based on the metal-catalyzed decomposition of hazardous, not easily accessible, diazo compounds.